The Practice of Legal and Tax Regulation of Land Relations in Agriculture in Russia - BAYNOVA, Maria S.; DYAKONOV, Michail U.; EVSTRATOVA, Tatiana A.; SIDYAK, Anastasia A. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
Land policy is the official activity of a government on its intentions and plans regarding the conservation, use, and allocation of land. Land relations are closely linked to property relations and environmental aspect of land usage. The main point is that land is a means of production in agriculture, and land relations are a part of agricultural policy in regions. Governmental policy is based on the legal approach and economic perspective of regulation. Statistical studies show the problem of land use for agriculture. The Russian Federation is the largest state in the world, however the acreage of agricultural land is being gradually reduced and the area of not used lands is enlarging. The tax system supports use of farmland for the purpose intended. At the same time local authorities could be interested in budget replenishment for current needs and, therefore, in increase of land tax. Taxes are rising for all arable land both used and unused. Based on the study of international practice we could offer up the successful land policy in the agriculture area.